ESTIMASI DAYA DUKUNG EKOLOGIS DAN PERSEPSI WISATAWAN DI KAWASAN WISATA KEMIT FOREST EDUCATION CILACAP JAWA TENGAH - Marni Marni; Fonny Rianawati; Khairun Nisa (Jurnal Sylva Scienteae, 2020)
The carrying capacity of ecological tourism is the ability of the area to accommodate tourists in a certain amount. The number of tourist visits that are abundant in a tourist attraction influences the ability to support ecological tourism and can have an impact on tourists. Kemit Forest Education is one of the tourist locations which has a high number of visits. This study aims to estimate the number of tourist visits and estimate the carrying capacity of ecological tourism and find out the perceptions of tourists about Kemit Forest Education tours. The method used in this study is qualitative data and quantitative data. The results of research on ecological tourism and tourist perceptions are the number of tourist visits in 2017 and 2018 respectively 120,707 person and 154,655 person and the carrying capacity of ecological tourism is 434 people per hectare and the needs of each tourist area is 23.04 m². Tourist perception states that the worst conditions in tourist sites are road conditions to tourist sites while the best conditions are in the availability of seats in tourist sites and good places to take picturesKeywords: Carrying capacity; tourism; perception